Program Feature-Based Benchmarking for Fuzz Testing - Miao, Miao; Kummita, Sriteja; Bodden, Eric; Wei, Shiyi (Proceedings of the ACM on Software Engineering)
Fuzzing is a powerful software testing technique renowned for its effectiveness in identifying software vulnerabilities. Traditional fuzzing evaluations typically focus on overall fuzzer performance across a set of target programs, yet few benchmarks consider how fine-grained program features influence fuzzing effectiveness. To bridge this gap, we introduce FeatureBench, a novel benchmark designed to generate programs with configurable, fine-grained program features to enhance fuzzing evaluations. We reviewed 25 recent grey-box fuzzing studies, extracting 7 program features related to control-flow and data-flow that can impact fuzzer performance. Using these features, we generated a benchmark consisting of 153 programs controlled by 10 fine-grained configurable parameters. We evaluated 11 fuzzers using this benchmark, with each fuzzer representing either distinct claimed improvements or serving as a widely used baseline in fuzzing evaluations. The results indicate that fuzzer performance varies significantly based on the program features and their strengths, highlighting the importance of incorporating program characteristics into fuzzing evaluations.

Species Knowledge About a UNESCO Natural World Heritage Site and the Importance of Connectedness with Nature - Puppe, Ricardo; Schmäing, Till (Heritage)
Species knowledge of local animal species is of great importance for one’s own environmental awareness and is a major component for managing present and future crises in education for sustainable development. For this reason, this study is the first to survey the species knowledge of visitors to the UNESCO Natural World Heritage Site the Wadden Sea of the North Sea, which is the largest mudflat area in the world. In this context, the self-assessment of the respondents and the extent of their connectedness with nature are also examined. To answer the research questions, a questionnaire survey was carried out to determine the species knowledge and degree of connectedness with nature. For data analysis, various statistical methods such as t-tests and correlation analyses were used. The results show that the 126 visitors to the Wadden Sea Visitor Centre have a rather low level of species knowledge. In this regard, the European Herring Gull is the only very well-known species among the respondents. In addition, a further construct was investigated in the form of connectedness with nature, between which a significant positive correlation was found with species knowledge.

Topology-optimized silicon nitride coupler for integrated single-photon emitters - Farheen, Henna; Chen, Yuheng; Chen, Peigang; Kryvobok, Artem; Peana, Samuel; Senichev, Alexander; Shalaev, Vladimir M.; Boltasseva, Alexandra; Förstner, Jens; Kildishev, Alexander V. (Photonic Computing: From Materials and Devices to Systems and Applications II)
We present a topology-optimized silicon nitride (Si3N4) coupler designed to enhance the coupling efficiency between integrated single-photon emitters and photonic waveguide modes. By leveraging inverse design techniques, we optimize the coupler’s geometry to maximize power transfer while maintaining fabrication feasibility by improving mode overlap and directional emission, addressing the challenge of low coupling efficiency caused by size mismatch and material incompatibility. Simulations demonstrate a substantial enhancement in photon extraction and waveguide coupling. This approach can be extended to other photonic devices, offering a versatile framework for improving quantum light-matter interactions in integrated photonics.
Keywords: tet_topic_waveguide

From demand to action: Analysing building emissions and refurbishment scenarios towards climate neutrality - Kirschbaum, Julia; Divkovic, Denis; Meschede, Henning (Applied Energy)

Sustainable finance down-to-earth? Insights from the German regional economy - Knoll, Lisa; Klüh, Ulrich; Naji, Ilias; Rossmann, Felix (Finance and Space)

Sustainable Finance und Soziologie - Knoll, Lisa (Sustainable Finance. Die Zukunft nachhaltigen Investierens – ein interdisziplinärer Ausblick)

Vom Muster in die Struktur: Ein Verfahrenskonzept der Wissenschaftskommunikation für die BBNE - Kiepe, Karina; Schlömer, Tobias (berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

Ab initio calculations of spin waves: A review of theoretical approaches and applications - Neugum, Michael; Schindlmayr, Arno (Materials)
Spin waves represent an important class of low-energy excitations in magnetic solids, which influence the thermodynamic properties and play a major role in technical applications, such as spintronics or magnetic data storage. Despite the enormous advances of ab initio simulations in materials science, quantitative calculations of spin-wave spectra still pose a significant challenge, because the collective nature of the spin dynamics requires an accurate treatment of the Coulomb interaction between the electrons. As a consequence, simple lattice models like the Heisenberg Hamiltonian are still widespread in practical investigations, but modern techniques like time-dependent density-functional theory or many-body perturbation theory also open a route to material-specific spin-wave calculations from first principles. Although both are in principle exact, actual implementations necessarily employ approximations for electronic exchange and correlation as well as additional numerical simplifications. In this review, we recapitulate the theoretical foundations of ab initio spin-wave calculations and analyze the common approximations that underlie present implementations. In addition, we survey the available results for spin-wave dispersions of various magnetic materials and compare the performance of different computational approaches. In this way, we provide an overview of the present state of the art and identify directions for further developments.

Generalized Miller formulae for quantum anharmonic oscillators - Meyer, Maximilian Tim; Schindlmayr, Arno (Dynamics)
Miller's rule originated as an empirical relation between the nonlinear and linear optical coefficients of materials. It is now accepted as a useful tool for guiding experiments and computational materials discovery, but its theoretical foundation had long been limited to a derivation for the classical Lorentz model with a weak anharmonic perturbation. Recently, we developed a mathematical framework which enabled us to prove that Miller's rule is equally valid for quantum anharmonic oscillators, despite different dynamics due to zero-point fluctuations and further quantum-mechanical effects. However, our previous derivation applied only to one-dimensional oscillators and to the special case of second- and third-harmonic generation in a monochromatic electric field. Here we extend the proof to three-dimensional quantum anharmonic oscillators and also treat all orders of the nonlinear response to an arbitrary multi-frequency field. This makes the results applicable to a much larger range of physical systems and nonlinear optical processes. The obtained generalized Miller formulae rigorously express all tensor elements of the frequency-dependent nonlinear susceptibilities in terms of the linear susceptibility and thus allow a computationally inexpensive quantitative prediction of arbitrary parametric frequency-mixing processes from a small initial dataset.

FreeBeacon: Efficient Communication and Data Aggregation in Battery-Free IoT - Liu, Gaosheng; Yıldırım, Kasım Sinan; Wang, Lin (IEEE Transactions on Mobile Computing)

WATS up? What About Teacher Shortage? International Perspectives from Denmark, Germany, and Sweden - Boström, Lena; Kreienbaum, Maria Anna; Wüllner, Sabrina; Ørsted Andersen, Frans; Bostedt, Göran; Håkansson Lindqvist, Marcia (Teacher Shortage in International Perspectives: Insights and Responses. Non-Traditional Pathways to the Teacher Profession)

Teacher Shortages in Germany – Causes, Countermeasures, and Assessments by Educational Scientists - Kreienbaum, Maria Anna; Wüllner, Sabrina (Teacher Shortage in International Perspectives: Insights and Responses. Non-Traditional Pathways to the Teacher Profession)

Frauen im Akkord. Marianne Herzog als Protokollantin westdeutscher Zustände - Vukadinovic, Vojin Sasa (Zeitschrift für Geschichtswissenschaft)

Künstliche Intelligenz in der Kriegsführung. Überblick, Hoffnungen und Risiken - Hälterlein, Jens (Marxistische Blätter)

Autonome Waffensysteme und Meaningful Human Control - Hälterlein, Jens (Marxistische Blätter)

KI im Krieg. „Wir brauchen mehr kritische Debatten und zivilgesellschaftliches Engagement“ - Hälterlein, Jens (NETZPOLITIK.ORG)

The Reinvention of the human body: Cyborgs, String Figures and New Boundaries - Grewe, Felix (Women and their Body)

Netzwerkanalysen als Bestandteil von Sportentwicklungsplanungen - Meier, Heiko; Peper, Robert; Kukuk, Marc; Wäsche, Hagen

MSL: Multi-class Scoring Lists for Interpretable Incremental Decision-Making - Heid, Stefan; Kornowicz, Jaroslaw; Hanselle, Jonas; Thommes, Kirsten; Hüllermeier, Eyke (Communications in Computer and Information Science)
Abstract A scoring list is a sequence of simple decision models, where features are incrementally evaluated and scores of satisfied features are summed to be used for threshold-based decisions or for calculating class probabilities. In this paper, we introduce a new multi-class variant and compare it against previously introduced binary classification variants for incremental decisions, as well as multi-class variants for classical decision-making using all features. Furthermore, we introduce a new multi-class dataset to assess collaborative human-machine decision-making, which is suitable for user studies with non-expert participants. We demonstrate the usefulness of our approach by evaluating predictive performance and compared to the performance of participants without AI help.

Breaking of the Up‐Down Symmetry of DNA Origami on a Solid Substrate - Velpula, Gangamallaiah; Tomm, Emilia; Shen, Boxuan; Mali, Kunal S.; Keller, Adrian Clemens; De Feyter, Steven (Angewandte Chemie International Edition)
Abstract Controlling the surface orientation of DNA origami nanostructures (DON) is crucial for applications in nanotechnology and materials science. While previous work utilized various DON modifications, simple methods for controlling their landing orientation remain scarce. Here, we demonstrate a straightforward approach to control the adsorption orientation of chiral double‐L (CDL) DON on mica by tuning magnesium ion (Mg 2 ⁺) concentration and exploiting global shape distortions. Using atomic force microscopy (AFM), we analyzed the resulting distribution of the mirror‐image orientations, referred to as S and Z orientations, at both buffer/mica and air/mica interfaces and identified conditions resulting in homogenous CDL orientation of 100% S. These results demonstrate how DON conformation and ionic environments influence DON orientation, offering insights for precise nanostructure deposition.